Sosialisasi Mitigasi Bencana Gempabumi Untuk Siswa Sekolah Dasar Di Kecamatan Nusaniwe Desa Seilale Kota Ambon - Abdi Pangestu; Joel K. Cols Cols; Siti R. Sehwaky; Fadila F F; Rumasoreng Rumasoreng; Ronald D. Hukubun (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Tectonically, Eastern Indonesia is a complex technonic area because it is formed due to the confluence of three large plates, namely the Eurasian Plate in the west, the Indian-Australian to the south and the Pacific Plate in the east known as the Triple Junction. This is what causes the Maluku area and its surroundings to have a high vulnerability to earthquakes and tsunamis. The importance of disaster preparedness to reduce casualties is the basis of this socialization activity. The core activity of learning disaster mitigation is the process of protecting yourself from disasters before and during disasters. This socialization took place through the presentation of material in the form of PowerPoint presentations in class. The material presented included the definition of an earthquake, the characteristics of the earthquake, what to do if an earthquake occurs in school, signs of an earthquake, and how to save yourself in the form of a song video. Based on the results of the socialization, the students determined that the cause of many casualties was the lack of knowledge about disaster mitigation in schools and the local environment early on.